INTEGRASI NILAI MULTIKULTURAL DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR - Lusia Mumtahanah (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
The integration of multicultural values ​​is a process to acquire the knowledge, the development of attitudes and behavior in order to live mutual respect, tolerance, full of peace, mutual aid, and non-violence. Islamic religious education is education that is focused more on the improvement of mental attitude manifested in deeds, both for the purposes of self and others, both theoretical and practical. This study three research focus, firstly any form of multicultural values ​​in the learning of Islamic religious education at SDN 1 Balun Turi Lamongan ?, Second, How is the implementation of multicultural values ​​in the learning of Islamic religious education ?, Third, How to enabling and inhibiting factors integration of value - the value of multicultural learning PAI at SDN 1 balun Turi Lamongan ?. The research is a qualitative descriptive approach. Collecting data through interviews, observation and documentation. The method is the data analysis data reduction, presentation of data, conclusion drawing / verification. The results of this study indicate that 1) Form of multicultural values ​​which are applied in the process of integration in which PAI learning Inclusive Value (Open), Human Values ​​(Humanist), the value of tolerance, the value of Please Help, the value of Justice (Democratic) and nuse values ​​Equality and Fraternity (brotherhood), 2) the implementation of the integration of multicultural values ​​in PAI learning done in the planning, implementation and evaluation of learning. 3) The supporting factors that exist as a unified educational curriculum, textbooks laden multicultural content and the enabling environment as well as religious. While the inhibiting factor is the lack of media diversity in the school environment, multicultural load content in the RPP is still less so is dominated environmental factors.